Evidence for multiple bulbar and higher brain circuits processing sensory inputs from the respiratory system in humans. (7th October 2020) - Farrell, Michael J.; Bautista, Tara G.; Liang, Emma; Azzollini, Damian; Egan, Gary F.; Mazzone, Stuart B.
Abstract : Key points: Unpleasant respiratory sensations contribute to morbidity in pulmonary disease. In rodents, these sensations are processed by nodose and jugular vagal sensory neurons, two distinct cell populations that differentially project to the airways and brainstem. Whether similar differences exist in bronchopulmonary sensory pathways in humans is unknown. We use functional magnetic resonance imaging during inhalation of capsaicin and ATP, showing that airway nodose pathways project centrally to the nucleus of the solitary tract, whereas jugular pathways input into the trigeminal brainstem nuclei. We also show differences between the efficacy of nodose and jugular stimuli to evoke cough and activity in motor control regions of the brain. Our data suggest that humans have two distinct vagal sensory neural systems governing airway sensations and this may have implications for the development of new antitussive therapies. Abstract: In rodents, nodose vagal sensory neurons preferentially innervate the distal airways and terminate centrally in the nucleus of the solitary tract. By contrast, jugular vagal sensory neurons preferentially innervate the proximal airways and terminate in the paratrigeminal nucleus in the dorsolateral medulla. This differential organization suggests distinct roles for nodose and jugular pathways in respiratory sensory processing. However, it is unknown whether bronchopulmonary afferent pathways are similarly arranged in humans. We set out to investigate this using high resolution brainstem and whole brain functional magnetic resonance imaging in healthy human participants when they were inhaling stimuli known to differentially activate nodose and jugular pathways. Inhalation of capsaicin or ATP evoked respiratory sensations described as an urge‐to‐cough, although ATP was significantly less effective compared to capsaicin at evoking the motor act of coughing. The nodose and jugular neuron stimulant capsaicin increased blood oxygen level‐dependent (BOLD) signals extending across the dorsomedial and dorsolateral medulla, encompassing regions containing both the nucleus of the solitary tract and the paratrigeminal nucleus. By contrast, at perceptually comparable stimulus intensities, the nodose‐selective stimulant ATP resulted in BOLD signal intensity changes that were confined to the area of the nucleus of the solitary tract. During whole brain imaging, capsaicin demonstrated a wider distributed network of activity compared to ATP, with significantly increased activity in regions involved with motor control functions. These data suggest that functional and neuroanatomical differences in bronchopulmonary nodose and jugular sensory pathway organization are conserved in humans and also that this has implications for understanding the neurobiological mechanisms underpinning cough. Key points: Unpleasant respiratory sensations contribute to morbidity in pulmonary disease. In rodents, these sensations are processed by nodose and jugular vagal sensory neurons, two distinct cell populations that differentially project to the airways and brainstem. Whether similar differences exist in bronchopulmonary sensory pathways in humans is unknown. We use functional magnetic resonance imaging during inhalation of capsaicin and ATP, showing that airway nodose pathways project centrally to the nucleus of the solitary tract, whereas jugular pathways input into the trigeminal brainstem nuclei. We also show differences between the efficacy of nodose and jugular stimuli to evoke cough and activity in motor control regions of the brain. Our data suggest that humans have two distinct vagal sensory neural systems governing airway sensations and this may have implications for the development of new antitussive therapies.